Implementation of a reference standard and proficiency testing programme by the World Wide Antimalarial Resistance Network (WWARN). - Lourens, C; Watkins, WM; Barnes, K; Sibley, C; Guerin, P; White, N; Lindegardh, N (BioMed Central, 2010)
BACKGROUND: The Worldwide Antimalarial Resistance Network (WWARN) is a global collaboration to support the objective that anyone affected by malaria receives effective and safe drug treatment. The Pharmacology module aims to inform optimal anti-malarial drug selection. There is an urgent need to define the drug exposure - effect relationship for most anti-malarial drugs. Few anti-malarials have had their therapeutic blood concentration levels defined. One of the main challenges in assessing safety and efficacy data in relation to drug concentrations is the comparability of data generated from different laboratories. To explain differences in anti-malarial pharmacokinetics in studies with different measurement laboratories it is necessary to confirm the accuracy of the assay methods. This requires the establishment of an external quality assurance process to assure results that can be compared. This paper describes this process. METHODS: The pharmacology module of WWARN has established a quality assurance/quality control (QA/QC) programme consisting of two separate components:1. A proficiency testing programme where blank human plasma spiked with certified reference material (CRM) in different concentrations is sent out to participating bioanalytical laboratories.2. A certified reference standard programme where accurately weighed amounts of certified anti-malarial reference standards, metabolites, and internal standards are sent to participating bioanalytical and in vitro laboratories. CONCLUSION: The proficiency testing programme is designed as a cooperative effort to help participating laboratories assess their ability to carry out drug analysis, resolve any potential problem areas and to improve their results - and, in so doing, to improve the quality of anti-malarial pharmacokinetic data published and shared with WWARN.By utilizing the same source of standards for all laboratories, it is possible to minimize bias arising from poor quality reference standards. By providing anti-malarial drug standards from a central point, it is possible to lower the cost of these standards.